Effective content management and delivery methods using open access strategy / Mohd Zahid Ismail - Ismail, Mohd Zahid (Institute of Graduate Studies, UiTM, 2013)
Existing content delivery strategies by incumbent service providers in Malaysia suppress new innovative value-added services as it eliminates opportunities for open partnership between network operators and thirdparty service providers. This creates a high barrier of entry of delivering new services that will substantially address the demand pull from wanting subscribers. This research examines elements of process innovation that contributes to improving broadband content delivery quality and addresses the demand pull for high quality contents by TV and broadband subscribers in Malaysia. Process innovation in the content delivery strategies impacting current business model of high speed broadband service delivery in Malaysia will be analyzed. This involves exploring contributing factors that affect the broadband and broadcast service providers’ Quality of Service (QoS) and the subscriber Quality of User Viewing Experience (QoE). This research analyzes the quality of the existing service delivery, reviewing the various content delivery methods and analyzing the Open Access network policies that advocates the participation of multiple service providers. This research also reviews the different types of multi-play services to subscribers which liberate them from proprietary contents and services. The cross section, ex post facto, formal empirical study involved interviewing 232 respondents whom are subscribers of the present broadband and broadcast service providers in the Klang Valley…